Silicon negative electrode material, preparation method of silicon negative electrode material, negative electrode plate, preparation method of negative electrode plate and all-solid-state battery

By forming a polybiphenyloxadiazole cladding layer on the surface of silicon particles of the silicon negative electrode material, the mechanical stress and capacity attenuation caused by volume expansion during the electrochemical cycle of the silicon negative electrode material is solved, extending the battery life and improving the battery life conductivity.

CN119481004APending Publication Date: 2025-02-18EVE ENERGY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411658056.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The silicon negative electrode material increases mechanical stress due to volume expansion during the electrochemical cycle, resulting in electrode crushing and capacity attenuation problems.

Method used

A polybiphenyloxadiazole coating is formed on the surface of silicon particles, and a precursor solution is formed by reaction of chlorammonia sulfuric acid and 4,4'-diphenyl acid, and react with silicon powder under specific conditions to form a porous structure Covering layer to alleviate stress and volume changes of silicon particles.

Benefits of technology

It effectively suppresses the capacity attenuation of the silicon negative electrode material during the cycle, extends the battery life, and improves the mechanical strength and electrical conductivity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a silicon negative electrode material, a preparation method of the silicon negative electrode material, a negative electrode plate, a preparation method of the negative electrode plate and an all-solid-state battery, the silicon negative electrode material comprises silicon particles and a coating layer, the surface of the silicon particles is coated with the coating layer, the coating layer is a polybiphenyl oxadiazole layer, and the coating layer is provided with a plurality of pores. By utilizing the silicon negative electrode material, the stress and volume change generated in the electrochemical cycle process of the silicon particles can be relieved, the problem of capacity fading caused by electrode crushing in the cycle of the silicon negative electrode is solved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a silicon negative electrode material, a method for preparing the silicon negative electrode material, a negative electrode sheet, a method for preparing the negative electrode sheet, and an all-solid-state battery. Background Art

[0002] In recent years, the energy crisis and environmental problems caused by the consumption of traditional fossil energy have become increasingly serious. Electrochemical energy storage as an energy conversion and storage device has become the focus of current research. Among them, batteries, as a typical representative of electrochemical energy storage, have been widely used in portable electronic devices and electric vehicles.

[0003] Among the anode materials of existing batteries, silicon (Si) has become a promising anode material for the next generation of lithium-ion batteries due to its high theoretical capacity, low environmental hazard and low discharge potential. Compared with the graphite anode used in most lithium batteries, Si anode can provide up to 10 times the capacity, thus meeting the growing demand for high-performance and long-lasting lithium-ion batteries in portable electronics, electric vehicles and grid storage systems. However, the volume of silicon will expand significantly during the cycle, which can cause mechanical stress and eventual electrode crushing, making the development of silicon anode face the problems of mechanical degradation and capacity decay during the cycle. Summary of the invention

[0004] The purpose of the present application is to provide a silicon negative electrode material, a method for preparing a silicon negative electrode material, a negative electrode sheet, a method for preparing a negative electrode sheet and an all-solid-state battery. The silicon negative electrode material can be used to alleviate the stress and volume change of silicon particles during the electrochemical cycle, solve the problem of capacity attenuation of the silicon negative electrode due to electrode crushing during the cycle, and extend the life of the battery.

[0005] An embodiment of the present application provides a silicon negative electrode material, including silicon particles and a coating layer, wherein the coating layer is coated on the surface of the silicon particles, the coating layer is a poly(diphenylene oxide) layer, and the coating layer has a plurality of pores.

[0006] In some embodiments, the coating layer is a multi-layered structure.

[0007] In some embodiments, the poly(biphenyloxadiazole) layer is prepared by reacting raw materials including hydrazine sulfate, 4,4′-diphthalic acid, and concentrated sulfuric acid.

[0008] The present application also provides a method for preparing a silicon negative electrode material, comprising:

[0009] Dissolve hydrazine sulfate and 4,4′-diphenyldicarboxylic acid in concentrated sulfuric acid to obtain a precursor solution;

[0010] Add silicon powder to the precursor solution and react at 100°C to 140°C to obtain a reaction product;

[0011] The reaction product is immersed in an extraction solvent to obtain a silicon negative electrode material.

[0012] The embodiment of the present application provides a method for preparing a silicon negative electrode material, using hydrazine sulfate and 4,4′-diphenyldicarboxylic acid to form a precursor solution of a coating layer, and adding silicon powder to the precursor solution so that the silicon powder can be evenly dispersed in the precursor solution. Then, the in-situ coating technology is used to polymerize the precursor solution in situ to form a poly(diphenylene oxide) layer, thereby achieving uniform formation of a poly(diphenylene oxide) coating layer on the surface of the silicon particles, avoiding the problem of low local electronic conductivity. Then, an extractant is used to extract the sulfuric acid remaining in the reaction product, so that the poly(diphenylene oxide) coating layer in the reaction product forms pores, thereby forming a poly(diphenylene oxide) coating layer with a porous structure on the silicon particles. Because the poly(diphenylene oxide) coating layer has good flexibility and mechanical strength as well as a three-dimensional layered porous structure, it can alleviate the stress and volume changes generated by the silicon particles during the electrochemical cycle, inhibit the formation of a new SEI (Solid Electrolyte Interface membrane), and thus avoid continuous Li + It reduces consumption and promotes the ion / electron transfer of the negative electrode, solving the capacity attenuation problem of the silicon negative electrode caused by electrode crushing during the cycle and extending the life of the battery.

[0013] In some embodiments, the mass ratio of hydrazine sulfate to 4,4′-diphthalic acid is (3-5): (3-7.5).

[0014] In some embodiments, the mass ratio of hydrazine sulfate to silicon powder is (3-5): (10-50).

[0015] In some embodiments, the extraction solvent is 1,4-dioxane.

[0016] In some embodiments, after the step of soaking the reaction product in the extraction solvent, the step of removing the extraction solvent is further included.

[0017] An embodiment of the present application also provides a negative electrode sheet, including a negative electrode current collector and a negative electrode layer covering the surface of the negative electrode current collector, wherein the negative electrode layer includes 50% to 90% of a silicon negative electrode material, 20% to 50% of a solid electrolyte, 5% to 10% of a conductive agent and 1% to 5% of a binder by mass of the negative electrode layer, wherein the silicon negative electrode material is the silicon negative electrode material prepared by the above-mentioned method for preparing the silicon negative electrode material, or the silicon negative electrode material is the above-mentioned silicon negative electrode material.

[0018] In some embodiments, the adhesive is a polyisobutylene adhesive.

[0019] The embodiment of the present application further provides a method for preparing a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet described above, and the method for preparing the negative electrode sheet comprises:

[0020] Taking silicon negative electrode material, solid electrolyte, conductive agent, binder and solvent, and mixing them under vacuum conditions to form negative electrode slurry;

[0021] A negative electrode current collector is provided, and a negative electrode slurry is coated on the surface of the negative electrode current collector. The dew point is controlled to be ≤-55° C. and the negative electrode is baked to form a negative electrode sheet, wherein the negative electrode slurry forms a negative electrode layer.

[0022] An embodiment of the present application also provides an all-solid-state battery, including a negative electrode sheet, an electrolyte membrane and a positive electrode sheet, the electrolyte membrane is arranged between the negative electrode sheet and the positive electrode sheet, the negative electrode sheet is the above-mentioned negative electrode sheet, or the negative electrode sheet is a negative electrode sheet prepared according to the above-mentioned negative electrode sheet preparation method.

[0023] In some embodiments, the electrolyte membrane is selected from any one of a halide electrolyte membrane, an oxide electrolyte membrane, a polymer electrolyte membrane, and a sulfide electrolyte membrane.

[0024] The present application provides a silicon negative electrode material, which is coated with a poly(diphenylene oxide) layer on the surface of silicon particles. Since the poly(diphenylene oxide) coating layer has good flexibility and mechanical strength and a three-dimensional layered porous structure, it can alleviate the stress and volume change of silicon particles during the electrochemical cycle, inhibit the formation of a new SEI (Solid Electrolyte Interface membrane), thereby avoiding continuous Li + It reduces consumption and promotes the ion / electron transfer of the negative electrode, solving the capacity attenuation problem of the silicon negative electrode caused by electrode crushing during the cycle and extending the life of the battery. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] According to the type of electrolyte, batteries include liquid batteries and solid-state batteries. Among them, liquid batteries use liquid electrolytes. Exemplarily, liquid batteries can be traditional lithium-ion batteries. Traditional lithium-ion batteries have become one of the research focuses due to their high energy density, long cycle life and environmental friendliness. At present, lithium-ion batteries have been widely used in fields such as portable electronic devices and electric vehicles, but their lack of safety has become increasingly prominent. Lithium-ion batteries use traditional organic liquid electrolytes, which have problems such as flammability, explosion, and easy leakage, which limit the development of lithium-ion batteries. Solid-state batteries use solid electrolytes instead of organic electrolytes, which are non-volatile, non-flammable, and non-leaking. They fundamentally solve the safety hazards of traditional lithium-ion batteries, and solid-state batteries have broad development prospects.

[0027] The embodiment of the present application provides an all-solid-state battery, comprising a positive electrode sheet, an electrolyte membrane and a negative electrode sheet, wherein the electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet.

[0028] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode layer covering the surface of the positive electrode current collector. The positive electrode layer may cover one side surface or both sides of the positive electrode current collector along the thickness direction. Exemplarily, the positive electrode current collector may be aluminum foil. The positive electrode layer includes a positive electrode active material, and the positive electrode active material may be selected from one of lithium cobalt oxide, lithium iron phosphate, and nickel cobalt oxide.

[0029] The electrolyte membrane can be selected from any one of a halide electrolyte membrane, an oxide electrolyte membrane, a polymer electrolyte membrane, and a sulfide electrolyte membrane. Further, in some embodiments, the electrolyte membrane is preferably a halide electrolyte membrane or a sulfide electrolyte membrane. Wherein, when the electrolyte membrane is a halide electrolyte membrane, the halide electrolyte has good chemical stability, and has strong anti-oxidation etching ability and electrochemical stability under high temperature and high pressure environment, thereby being able to improve the reliability and long-term service life of the battery system. In addition, the halide electrolyte membrane also has good electrical and mechanical properties, wherein the high mechanical strength of the halide electrolyte membrane enables it to effectively resist external forces and stresses, thereby being able to enhance the structural stability of the battery system. In addition, the halide electrolyte membrane has the convenience of the preparation process, and the halide electrolyte membrane does not produce toxic gases such as H2S during the preparation process, so a strict inert atmosphere is not required. In theory, the generation of by-products can be avoided by ensuring that the environment is dry enough, which is suitable for large-scale industrial production.

[0030] Among them, when the electrolyte membrane is a sulfide electrolyte, on the one hand, the sulfide solid electrolyte can show extremely high ionic conductivity, close to the conduction efficiency of traditional liquid electrolytes, thus meeting the urgent needs of modern applications for high-power density batteries. On the other hand, compared with other types of solid-state batteries, the sulfide solid-state battery assembled with sulfide electrolyte membranes has achieved significant optimization in energy density. After multiple charge and discharge cycles, the sulfide solid-state battery can still maintain a high capacity, showing better cycle stability than oxide solid-state batteries.

[0031] The negative electrode sheet includes a negative electrode current collector and a negative electrode layer covering the surface of the negative electrode current collector. The negative electrode layer may cover one side surface or both sides of the negative electrode current collector along the thickness direction. Exemplarily, the negative electrode current collector may be a copper foil. The negative electrode layer includes a negative electrode active material. When the negative electrode active material is silicon, the problem of silicon expansion may occur.

[0032] To solve the silicon expansion problem, we can try to form a protective coating on the surface of the silicon material to slow down the volume expansion of silicon. Among them, when the protective coating is a carbon coating, the carbon coating can improve the conductivity and buffer the volume change. However, silicon with a thick buffer carbon layer shows a relatively low capacity. When the protective layer is a polymer coating, the polymer coating includes polypyrrole, polyaniline, polyacrylic acid and poly (3,4-ethylenedioxythiophene). The polymer coating has insulation and working potential mismatch, which will cause the composite electrode to be easily polarized, and ultimately make the battery have low capacity and short life.

[0033] To solve the above problems, an embodiment of the present application provides a negative electrode sheet. Based on the mass of the negative electrode layer, the negative electrode layer in the negative electrode sheet includes 50% to 90% of silicon negative electrode material, 20% to 50% of solid electrolyte, 5% to 10% of conductive agent and 1% to 5% of binder.

[0034] Among them, the silicon negative electrode material includes silicon particles and a coating layer, and the coating layer is coated on the surface of the silicon particles. In the embodiment of the present application, the coating layer is a poly(diphenylene oxide) layer, and the coating layer has a plurality of pores. Among them, poly(diphenylene oxide) is also called biphenyl-poly(diphenylene oxide). In the embodiment of the present application, the poly(diphenylene oxide) layer is a conductive polymer layer, which is a multi-layered layered structure and a porous structure with mixed ion / electronic conductors. Exemplarily, the poly(diphenylene oxide) layer can be made by reacting raw materials including hydrazine sulfate, 4,4′-diphthalic acid and concentrated sulfuric acid.

[0035] Exemplarily, the solid electrolyte may be a halide solid electrolyte or a sulfide solid electrolyte. Exemplarily, the halide solid electrolyte includes but is not limited to: at least one of Li2FeCl4, Li2CdCl4, Li2MgCl4, LiScF4, LiYF4, Li3InBr6, Li3InCl6, Li2CdCl4, and Li2ZnCl4. The sulfide solid electrolyte includes but is not limited to Li7P 2.9 Mn 0.1 S 10.7 I 0.3 , Li 10 GeP2S 12 , Li 10 SiP2S 12 、Li6PS5Cl、Li7Ge3PS 12 , Li 6.6 P 0.4 Ge 0.6 At least one of S5I.

[0036] Exemplarily, the conductive agent may be graphite, Super-P (conductive carbon black), acetylene black, Ketjen black, vapor-grown carbon fiber, carbon nanotube, graphene, and the like.

[0037] For example, the binder may be polyisobutylene binder, HNBR (hydrogenated nitrile rubber), SEBS (hydrogenated styrene-butadiene block copolymer), PVDF (polyvinylidene fluoride), or the like.

[0038] In the negative electrode sheet provided by the embodiment of the present application, the polybiphenyl oxadiazole coating layer in the silicon negative electrode material of the negative electrode layer can passivate the negative electrode-solid electrolyte interface to form a stable SEI, thereby significantly improving the cycle stability of the assembled battery. In addition, by adding a solid electrolyte to the negative electrode layer and controlling the addition amount of the solid electrolyte to be 20% to 50%, on the one hand, the solid electrolyte can improve the ionic conductivity, thereby improving the energy density of the assembled battery, and on the other hand, it can avoid the problem that the effect is not obvious due to too little addition of the solid electrolyte, or the energy density of the battery is reduced due to too much addition of the solid electrolyte. In addition, by adding a conductive agent to the negative electrode layer and controlling the addition amount of the conductive agent to be 5% to 10%, on the one hand, the conductive agent can provide an electron transmission path to improve the electron conductivity, thereby helping to reduce the resistance of the negative electrode sheet, and then helping to improve the energy density of the assembled battery, on the other hand, it can avoid the problem that the resistance of the negative electrode sheet is too large due to too little addition of the conductive agent, or the energy density of the battery is reduced due to too much addition of the conductive agent, and the conductive agent may react with the solid electrolyte (such as sulfide). In addition, by adding a binder to the negative electrode layer, the binder can be used to bond the various components in the negative electrode layer together to form a whole, and tightly connect them to form a pole piece. At the same time, the amount of binder added is controlled to avoid too little binder causing the negative electrode piece to shed powder, or too much binder which easily increases the impedance of the negative electrode piece, thereby affecting the electrical performance of the battery.

[0039] The present application also provides a method for preparing the negative electrode sheet, comprising:

[0040] Step S1: Take silicon negative electrode material, solid electrolyte, conductive agent, binder and solvent, and mix them under vacuum conditions to form negative electrode slurry.

[0041] In this embodiment, according to the mass of the negative electrode slurry, 50% to 90% of silicon negative electrode material, 20% to 50% of solid electrolyte, 5% to 10% of conductive agent, 1% to 5% of polyisobutylene binder and p-xylene solvent are weighed and passed through a vacuum stirring device to form a uniform and stable negative electrode slurry. Among them, the polyisobutylene binder is a solution with a solid content of 3% to 8% prepared by dissolving polyisobutylene in p-xylene.

[0042] Step S2, providing a negative electrode current collector, coating the negative electrode slurry on the surface of the negative electrode current collector, controlling the dew point to ≤-55°C and baking to form a negative electrode sheet, wherein the negative electrode slurry forms a negative electrode layer.

[0043] In this embodiment, the negative electrode slurry is coated on the carbon-coated aluminum foil and baked at 90°C for 12 hours to form the negative electrode sheet. In this step, the dew point is controlled and the dew point is required to be ≤-55°C. In addition, the dew point is controlled to be ≤-55°C during the baking process. On the one hand, it ensures that the production is carried out in a dew point controlled environment to avoid water absorption of materials such as conductive agents, and meet the battery system's requirements for strict water control. On the other hand, by strictly controlling the environmental dew point, electrolytes such as sulfide electrolytes can be prevented from reacting in a humid environment to produce toxic hydrogen sulfide gas.

[0044] The present application also provides a method for preparing a silicon negative electrode material, comprising:

[0045] Step P1: dissolve hydrazine sulfate and 4,4′-diphenyldicarboxylic acid in concentrated sulfuric acid to obtain a precursor solution.

[0046] In this embodiment, hydrazine sulfate and 4,4′-diphenyl dicarboxylic acid are dissolved in concentrated sulfuric acid (fuming oil), and stirred in a 75°C oil bath for 8-12 hours to ensure that all solids are dissolved and the solution is evenly mixed to obtain a precursor solution. Among them, the mass ratio of hydrazine sulfate: 4,4′-diphenyl dicarboxylic acid = (3-5): (3-7.5). After experimental verification, the effect is best within this ratio range. Exemplarily, the amount of hydrazine sulfate added is 300g to 500g. The amount of 4,4′-diphenyl dicarboxylic acid added is 300g to 750g. In some embodiments, preferably, the amount of hydrazine sulfate added is 400g, and the amount of 4,4′-diphenyl dicarboxylic acid added is 600g.

[0047] Step P2: adding silicon powder to the precursor solution, and reacting at 100° C. to 140° C. to obtain a reaction product.

[0048] In this embodiment, silicon powder is added to the precursor solution, and stirred at high speed for 5 hours under heating at 120°C to ensure that the precursor solution and the negative electrode material silicon powder are evenly mixed and react fully. The precursor solution is reacted to obtain a coating layer. The mass ratio of silicon powder: hydrazine sulfate = (3-5): (10-50). After experimental verification, the effect is best within this ratio range. Exemplarily, the amount of silicon powder added is 1 kg to 5 kg. In some embodiments, preferably, the amount of silicon powder added is 3 kg.

[0049] Step P3: Soaking the reaction product in an extraction solvent to obtain a silicon negative electrode material.

[0050] In this embodiment, the extraction solvent is 1,4-dioxane. Specifically, the obtained reaction product is soaked in 1,4-dioxane for 12 hours to extract the sulfuric acid remaining in the reaction product and to make the material of the reaction product grow pores to obtain a porous silicon negative electrode material.

[0051] In the embodiment of the present application, after the step of immersing the reaction product in the extraction solvent, a step of removing the extraction solvent is also included.

[0052] Specifically, in this embodiment, deionized water is used for washing to remove 1,4-dioxane (wherein 1,4-dioxane is also called 1,4-dioxane), the washing liquid becomes neutral, and then dried in a vacuum oven at 80° C. for 24 hours to obtain a coated silicon negative electrode material.

[0053] The embodiment of the present application provides a method for preparing a silicon negative electrode material, using hydrazine sulfate and 4,4′-diphenyldicarboxylic acid to form a precursor solution of a coating layer, and adding silicon powder to the precursor solution so that the silicon powder can be evenly dispersed in the precursor solution. Then, the in-situ coating technology is used to polymerize the precursor solution in situ to form a poly(diphenylene oxide) layer, thereby achieving uniform formation of a poly(diphenylene oxide) coating layer on the surface of the silicon particles, avoiding the problem of low local electronic conductivity. Then, an extractant is used to extract the sulfuric acid remaining in the reaction product, so that the poly(diphenylene oxide) coating layer in the reaction product forms pores, thereby forming a poly(diphenylene oxide) coating layer with a porous structure on the silicon particles. Because the poly(diphenylene oxide) coating layer has good flexibility and mechanical strength as well as a three-dimensional layered porous structure, it can alleviate the stress and volume changes generated by the silicon particles during the electrochemical cycle, inhibit the formation of a new SEI (Solid Electrolyte Interface membrane), and thus avoid continuous Li + The consumption of the negative electrode sheet is improved, and the ion / electron transfer of the negative electrode sheet is promoted at the same time, which solves the problem of capacity attenuation of the silicon negative electrode due to electrode crushing during the cycle, and prolongs the life of the battery. The silicon negative electrode material obtained by the preparation method of the present application can simultaneously improve the electronic and ionic conductivity, wherein the double-layer coating structure simultaneously improves the mechanical strength and improves the performance of the battery, and is suitable for application in an all-solid-state battery system.

[0054] The silicon negative electrode material, the negative electrode sheet formed by the silicon negative electrode material, and the all-solid-state battery formed by assembling the negative electrode sheets provided in the embodiments of the present application are described in detail below in conjunction with specific embodiments.

[0055] Examples 1-3

[0056] Example 1 provides an all-solid-state battery, which is prepared according to the following steps:

[0057] Step 1: Preparation of precursor solution: Dissolve 300-500 g of hydrazine sulfate and 300-750 g of 4,4′-diphenyldicarboxylic acid in fuming oil, and stir in an oil bath at 75°C for 8-12 h to ensure that all the solids are dissolved and the solution is evenly mixed.

[0058] Step 2: Coating of silicon materials: Take 1-5 kg ​​of silicon powder and add it to the above-mentioned precursor solution. Stir at high speed for 5 hours under heating at 120°C to ensure that the precursor solution and the positive electrode material are evenly mixed and fully reacted. Then, soak the obtained product in 1,4-dioxane for 12 hours to extract the residual sulfuric acid in the reaction product and make the material of the reaction product grow pores. Finally, wash with deionized water to remove 1,4-dioxane, the washing liquid becomes neutral, and then dry in a vacuum oven at 80°C for 24 hours to obtain the coated silicon negative electrode material.

[0059] Step 3, preparation of negative electrode sheet: weigh the above-mentioned coated silicon negative electrode material (50%-90%), solid electrolyte (20%-50%), conductive agent (5%-10%), polyisobutylene binder (1-5%) (dissolved in para-xylene to prepare a solution with a solid content of 3%-8%) and solvent para-xylene, and pass through a vacuum stirring device to form a uniform and stable negative electrode slurry, and apply the negative electrode slurry on a carbon-coated aluminum foil, and bake at 90°C for 12 hours to form a negative electrode sheet. Dew point control is carried out in this step, and the dew point is required to be ≤-55°C.

[0060] Step 4: Assembly of all-solid-state soft-pack batteries: die-cut the above-mentioned negative electrode sheet, and then stack, package, hot-press, cold-press and other steps with the electrolyte membrane and the positive electrode sheet to obtain the prepared all-solid-state soft-pack battery.

[0061] Comparative Example 1-3 provides an all-solid-state battery, which is different from Example 1-3 in that the silicon negative electrode material is silicon powder and does not contain a poly(diphenylamine) coating layer.

[0062] The all-solid-state batteries obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to cycle performance tests, and the results are shown in Table 1.

[0063] Table 1 Performance of all-solid-state batteries of Examples 1-3 and Comparative Examples 1-3

[0064]

[0065] As can be seen from Table 1, the silicon negative electrode material in the all-solid-state battery of Comparative Example 1-3 does not contain a poly(diphenylene oxide) coating layer, and the capacity retention rate of the obtained all-solid-state battery is low. By comparing Example 1-3 with Comparative Example 1-3, the surface of the silicon particles in the silicon negative electrode material in the all-solid-state battery of Example 1-3 is coated with a poly(diphenylene oxide) coating layer, which can effectively improve the capacity retention rate of the battery. The experimental results show that the use of a poly(diphenylene oxide) coating layer to coat silicon particles can alleviate the stress and volume changes generated by silicon particles during the electrochemical cycle, solve the problem of capacity attenuation caused by electrode crushing during the cycle of the silicon negative electrode, and extend the life of the battery.

[0066] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A silicon negative electrode material, characterized in that: The invention comprises silicon particles and a coating layer, wherein the coating layer is coated on the surface of the silicon particles, the coating layer is a polybiphenyl oxadiazole layer, and the coating layer has a plurality of pores.

2. The silicon negative electrode material according to claim 1, characterized in that: The coating layer is a multi-layered structure.

3. The silicon negative electrode material according to claim 1 or 2, characterized in that: The polybiphenyl oxadiazole layer is prepared by reacting raw materials including hydrazine sulfate, 4,4'-diphthalic acid and concentrated sulfuric acid.

4. A method for preparing a silicon negative electrode material, characterized in that: include: Dissolve hydrazine sulfate and 4,4′-diphenyldicarboxylic acid in concentrated sulfuric acid to obtain a precursor solution; Adding silicon powder to the precursor solution, reacting at 100° C. to 140° C. to obtain a reaction product; The reaction product is immersed in an extraction solvent to obtain a silicon negative electrode material.

5. The method for preparing a silicon negative electrode material according to claim 4, characterized in that: The mass ratio of the hydrazine sulfate to the 4,4′-diphthalic acid is (3-5): (3-7.5).

6. The method for preparing a silicon negative electrode material according to claim 4, characterized in that: The mass ratio of the hydrazine sulfate to the silicon powder is (3-5): (10-50).

7. The method for preparing a silicon negative electrode material according to any one of claims 4 to 6, characterized in that: The extraction solvent is 1,4-dioxane.

8. The method for preparing a silicon negative electrode material according to any one of claims 4 to 6, characterized in that: After the step of soaking the reaction product in the extraction solvent, the method further comprises the step of removing the extraction solvent.

9. A negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode layer covering the surface of the negative electrode current collector, and based on the mass of the negative electrode layer, the negative electrode layer includes 50% to 90% of a silicon negative electrode material, 20% to 50% of a solid electrolyte, 5% to 10% of a conductive agent and 1% to 5% of a binder, wherein the silicon negative electrode material is the silicon negative electrode material according to any one of claims 1 to 3, or the silicon negative electrode material is the silicon negative electrode material prepared according to the preparation method according to any one of claims 4 to 8.

10. The negative electrode sheet according to claim 9, characterized in that: The adhesive is a polyisobutylene adhesive.

11. A method for preparing a negative electrode sheet, characterized in that: The negative electrode sheet is the negative electrode sheet according to claim 9 or 10, and the preparation method of the negative electrode sheet comprises: Taking the silicon negative electrode material, the solid electrolyte, the conductive agent, the binder and the solvent, and mixing them under vacuum conditions to form a negative electrode slurry; A negative electrode current collector is provided, the negative electrode slurry is coated on the surface of the negative electrode current collector, the dew point is controlled to be ≤-55° C. and baked to form a negative electrode sheet, wherein the negative electrode slurry forms the negative electrode layer.

12. An all-solid-state battery, characterized in that: It comprises a negative electrode sheet, an electrolyte membrane and a positive electrode sheet, wherein the electrolyte membrane is arranged between the negative electrode sheet and the positive electrode sheet, and the negative electrode sheet is the negative electrode sheet according to claim 9 or 10, or the negative electrode sheet is the negative electrode sheet prepared according to the preparation method of the negative electrode sheet according to claim 10.

13. The all-solid-state battery according to claim 12, characterized in that: The electrolyte membrane is selected from any one of a halide electrolyte membrane, an oxide electrolyte membrane, a polymer electrolyte membrane, and a sulfide electrolyte membrane.

Citation Information

Patent Citations

  • Materials for electrochemical cells and methods of making and using same

    CN110870104A

  • Silicon-doped lithium-supplementing negative electrode plate, preparation method thereof and lithium ion battery

    CN114156554A

  • Composite negative plate, preparation method thereof and lithium metal secondary battery

    CN114430023A

  • Solid electrolyte-electrode complex as well as preparation method and application thereof

    CN115395077A

  • Negative electrode-solid electrolyte subassembly, all-solid secondary battery, and method for preparing all-solid secondary battery

    CN116137318A